HAKIKAT DAN URGENSI MODERNISASI DALAM KONTEKSTUALISASI PEMAHAMAN ISLAM DI ERA INDUSTRI 4.0 - Ansari (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2021)
At that time, the modernization affects all aspects of life, including social life, lifestyle, and morality. Constant innovation has resulted in technology that are increasingly complex. In fact, the project of a large-scale built on top of the main pillars of reflection, science, and science. Respect for the human and the material are very important and well worth it for the progress of human life. It only became clear in its development. This is the process that ultimately brings problems and more complex problems. And inequality serious in human life. Driven by the progress of science and technology, the changing times ushering in the era of progress, provide many benefits and convenience for mankind. Modernity is the result of the progress of the European community in the field of science and technology, which allows the community to control himself and his life. Centralism theological (the strength of the Lord) who controlled the church in the Middle ages was replaced by the doctrine of life centered on human (anthropocentrism). A new way of life that is different from time immemorial, how to trust, many of which are received that modernity is the culmination of the history of the development of human civilization.